From Flash in the Pan to Continuous Ban: How the Power of Theory of Planned Behavior in Continuous Boycott Intention - Sarah Awliya Dini; Rifelly Dewi Astuti (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
This study aims to analyze the role of Theory of Planned Behavior (TPB) and religiosity in influencing Continuous Boycott Intention toward Israeli-affiliated fast-food restaurants, in Indonesia. Utilizing the statistical analysis method of Structural Equation Modeling - Partial Least Squares (SEM-PLS), this study involved 400 respondents to test the validity of previously formulated hypotheses. The research results showed that (1) Religious Animosity and Perceived Success Likelihood have a significant positive impact on Attitude toward Boycott; (2) Attitude toward Boycott and Perceived Behavioral Control of Boycott have a significant positive impact on Continuous Boycott Intention, while Brand Loyalty has a significant negative impact on Continuous Boycott Intention; (3) Subjective Norm on Boycott and Motivation to Comply have a non-significant positive impact on Continuous Boycott Intention. Data was obtained from an independent survey with an online questionnaire, then analyzed through Wording Test, Pre-Test, and Main Test. The results of the analysis showed that all variables had good validity and reliability.